Faktor-Faktor Yang Mempengaruhi Kepuasan Dan Loyalitas Mahasiswa (Studi Kasus Pada Perguruan Tinggi Swasta Di Jakarta) - Mohamad Saparudin; Bambang Rahardjo (STMIK Mardira Indonesia, Bandung, 2018)
Increasingly intense competition among universities demands good knowledge and strategy from all universities to attract prospective students. For use in the education industry, reference is required on the values consisting of three factors, namely: Quality, Price, and Service. This research is the satisfaction and loyalty of students by several factors, namely price equity and SERQUAL. The results of the study showed that the sensation of sensitivity to loyalty and attitude as mediation by perception of the price of justice, and SERQUAL. The Serqual construct directly affects student loyalty and the directness of pricing justice also affects student loyalty. and the price of justice has the greatest effect compared to other constructs. Keyword : Price fairness, SErqual,.